Claiming the Politics of Articulation through Agency and Wholeness in Two Afro-Hispanic Postcolonial Narratives. - Castro-Borrego, Silvia Pilar (Bridgewater State University, 2016)
Following a context-based approach and the tenets of post-positivist realist theory, this paper will analyze two post-colonial Afro-Spanish novels immersed in the context of the African Diaspora: María Nsue Angüe’s Ekomo (1983) and Michelline Dusseck’s Caribbean Echoes (1997). As part of the Diaspora Literacy, these texts will be read employing the search for wholeness as a theoretical tool, towards an epistemology of anti-colonial feminist struggle. These texts take active part in a decolonizing process that fosters a definition and vision of agency which makes wholeness possible, becoming an active expression of Black women’s spirituality across the African Diaspora. Both novels are written in Spanish, thus their classification as Afro-Hispanic. The texts are a mixture of traditional African elements inserted in European contexts; for this reason they will be studied as part of migrant literature, configuring as minor literature. Both writers the first from Ecuatorial Guinea, and the second from Haiti, follow the paradigm of the suppression of silence, in a process that relocates the word to do the telling from an original, agentive point of view. They share a compromise to disassemble the paradigm of resistance and replace it with the paradigm of growth, following a democracy of narrative participation. Presenting alternative ways of knowing that emerge from their femaleness and which may differ from the deconstructionist narratives produced by post-colonial male writers, they build a constructionist discourse. Relying in their “oraliterature,” they move from their communities to the community of readers. These writers affirm the place of Black women as creative artists who have fought not only the racism of the dominant culture but also the sexism of their own men.
" University repositories: The JIWS allows republication of articles and other publication genres in university repositories with proper citation of the JIWS. It is not necessary to contact us to download a JIWS and deposit it in a university repository." Política de acceso abierto tomada de: https://vc.bridgew.edu/jiws/policies.html
Keywords: Descolonización - En la literatura; Caribbeannes; Post-positivist Realist Theory; Diaspora literacy; Paradigm of Growth; Politics of Articulation; Decolonization